Stratigraphy, paleontology and age of Las Ventanas Formation (Neoproterozoic, Uruguay) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Las Ventanas Formation (FmLV), defined and mapped by Midot (1984), is composed by a thick, finingand thinning-upward sequence covering an area in excess of 120 km2 of the southern Nico Perez Terrane, Uruguay (Fig. 1). The structure in its type area corresponds to an ample syncline (Cerro Las Ventanas Syncline) with an axis oriented S20W (Figs. 2, 7f). Las Ventanas Formation is here subdivided into the following members: La Rinconada Member, Quebrada de Viera Member and El Perdido Member (Figs. 2, 4-5). La Rinconada Member is made up of basic volcanics, mainly basalts, vulcanoclastic breccias and subordinate basic tuffs, reaching 500 m in thickness (Fig. 6). It is overlain with erosional unconformity by the Quebrada de Viera Member, which is composed by polymictic conglomerates, grading to conglomerate-sandstone intercalations up section (Fig. 7a-d). Maximum thickness reaches 3800 m. Lithoclast composition shows provenance from a mixed volcanic (basic and acid) and granitic source area (Fig. 8a-b). Whereas basalt clasts are more common at the base, rhyolitic clasts and intercalated rhyolitic tuffs occur at the top of the Quebrada de Viera Member (Fig. 5). The overlying El Perdido Member (600 m measured thickness) is characterized by laminated siltstones and shales (Figs. 7e-f, 9), showing reddish colours at the base and green and grey colours at the top. Abundant pyrite at the top of this Member indicates disoxic or anoxic conditions (Fig 7e-8d). Thus, Las Ventanas Formation represents a deepening-upward sequence, recording evolution from an alluvial fan-dominated environment to shallow marine conditions with occasional storms indicated by hummocky cross stratification at the top of Quebrada de Viera Member (Fig. 9). Petrography shows compositional and textural immaturity of conglomerates and sandstones which together with sedimentary structures point to a steep palaeorelief.Las Ventanas Formation is intruded by syenites of the Sierra de Animas Formation, which yielded a Rb- Sr age of 520 ± 5 Ma, and also by the Pan de Azúcar Granite (559 ± 28 Ma, Rb-Sr). K-Ar datings of 572 ± 7 Ma obtained for synkinematic muscovites crystallized along the Puntas del Pan de Azúcar Thrust, suggest a minimum Vendian age for the unit (Figs. 1-2).A number of organic-walled microfossils is described for the first time, namely: Leiosphaeridia tenuissima, Leiosphaeridia minutissima, Lophosphaeridium sp., Soldadophycus bossii, Soldadophycus major, Soldadophycus sp., Vendotaenia sp (Fig. 11). The assemblage is characterized by its low diversity, abundance and large size (up to 400 µm) of Leiosphaeridia. Wrinkle structures occur in the upper El Perdido Member (Fig. 9). Based on the microfossils and the available datings, we assign Las Ventanas Formation to the Ediacaran (lower Vendian, ca. 600 Ma). The Playa Hermosa Formation is in tectonic contact with Las Ventanas Formation, and can be interpreted as a lateral facies or -alternatively- be younger than the latter unit (Fig. 12). On the basis of their microfossil assemblages, we envisage that Las Ventanas Formation immediately predates the Arroyo del Soldado Group which represent a thick shelf succession deposited in the upper Ediacaran between 580 and 535 Ma.An extensional geotectonic setting, possibly a rift, is postulated for Las Ventanas Formation. In favour of this hypothesis argue the bimodal (rhyolitic and basaltic), synsedimentary volcanism, steep palaeorelief, great thickness of alluvial fan conglomerates with more than 3500 m of psephitic sediments and the evolution from continental to open marine environments. A number of magmatic units may be associated to this extensional event, including the Nico Pérez Dyke Swarm (581 ± 13 Ma) and the Puntas del Santa Lucía Batholith (633 ± 10 Ma).
Keywords: Neoproterozoic; Vendian; Ediacaran; Acritarchs; Uruguay.